1997
DOI: 10.1063/1.118493
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in InGaN thick films and formation of InGaN/GaN double heterostructures in the entire alloy composition

Abstract: We report the growth of InGaN thick films and InGaN/GaN double heterostructures by molecular beam epitaxy at the substrate temperatures 700–800 °C, which is optimal for the growth of GaN. X-ray diffraction and optical absorption studies show phase separation of InN for InxGal−xN thick films with x>0.3. On the other hand, InxGal−xN/GaN double heterostructures show no evidence of phase separation within the detection capabilities of our methods. These observations were accounted for using Stringfellow’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
269
2
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 475 publications
(287 citation statements)
references
References 13 publications
15
269
2
1
Order By: Relevance
“…The F M (1) and F M (2) are the corrections given by Martin with respect to the original Keating model. F X (1) and F X (2) represent the additional corrections if the change of the d parameter is considered. From Eqs.…”
Section: ͑7͒mentioning
confidence: 99%
See 1 more Smart Citation
“…The F M (1) and F M (2) are the corrections given by Martin with respect to the original Keating model. F X (1) and F X (2) represent the additional corrections if the change of the d parameter is considered. From Eqs.…”
Section: ͑7͒mentioning
confidence: 99%
“…An important issue for In x Ga 1Ϫx N alloys is homogeneity: Experimentally it has been found that these alloys are often unstable against phase separation, spatial fluctuations in the In concentration, or partial ordering. [1][2][3][4] These effects have been shown to strongly affect the luminescence efficiency. It is therefore crucial to get a deeper insight into the energetics and local atomic structure of In x Ga 1Ϫx N alloys.…”
Section: Introductionmentioning
confidence: 99%
“…8 Our XRD measurements clearly indicate strong indium aggregation processes in our sample and this observation is in agreement with previous reports. [4][5][6][7][8] The comments also argued the interpretation of our scanning electron microscopy ͑SEM͒ and energy dispersive x-ray spectrometry ͑EDS͒ results. Our InGaN films have been found to have mirrorlike surface by scanning electron microscopy ͑SEM͒ and transmission electron microscopy ͑TEM͒ measurements.…”
mentioning
confidence: 99%
“…This result has been widely discussed in the nitride materials. [4][5][6][7] The correspondence of the appearance of multiple x-ray diffraction peaks in InGaN thin film to the phase separation over the surface has been clearly established. It has also been shown to correlate with double luminescence peaks.…”
mentioning
confidence: 99%
See 1 more Smart Citation